The Effect Job Insecurity, Work Flexibility, and Cyberloafing Behavior on Employee Performance (Case Study of Generation Z in Solo) - Muhammad Faiz Fauzan; Edy Purwo Saputro (Dinasti Review, 2025)
This study digs into how job insecurity, work flexibility, and cyberloafing shape employee performance among Generation Z workers in Solo. The research took a quantitative approach, gathering data from 110 participants who completed questionnaires distributed via Google Forms. Purposive sampling was used to select participants, and their responses were measured using a five-point Likert scale. Data analysis was handled through SPSS, which included running validity and reliability tests, checking classical assumptions, and testing hypotheses with multiple linear regression analysis. What emerged from the findings is that job insecurity doesn't really move the needle on employee performance, but work flexibility clearly does it has a strong positive impact. Cyberloafing behavior, meanwhile, doesn't seem to matter much either way. The takeaway here is that offering Generation Z employees flexible work arrangements can genuinely boost their performance, while concerns about job insecurity and cyberloafing behavior turn out to be less influential than one might expect.